2022
DOI: 10.3332/ecancer.2022.1433
|View full text |Cite
|
Sign up to set email alerts
|

Women’s cancers in Sudan with a focus on cervical cancer: turmoil, geopolitics and opportunities

Abstract: Cancer is the leading cause of death worldwide and the second leading cause of death in Sudanese women. However, despite proven interventions for primary, secondary and tertiary prevention and the World Health Organization's call to action toward eliminating cervical cancer, there has been little progress in addressing the cervical cancer burden in Sudan. This short communication intends to shed light on the challenges facing women's cancers in Sudan, taking cervical cancer as an example. It also discusses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 15-17 While cancer control programs typically aim for a patient delay of 30 or 14 days, 13 , 18 the absence of a national breast cancer screening program in Sudan makes achieving this goal challenging. 19 The frequently reported reasons for patients delay in this study were underestimating breast symptoms, lacking awareness about breast cancer and misinterpreting symptoms. Similar reasons were reported in LMICs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“… 15-17 While cancer control programs typically aim for a patient delay of 30 or 14 days, 13 , 18 the absence of a national breast cancer screening program in Sudan makes achieving this goal challenging. 19 The frequently reported reasons for patients delay in this study were underestimating breast symptoms, lacking awareness about breast cancer and misinterpreting symptoms. Similar reasons were reported in LMICs.…”
Section: Discussionmentioning
confidence: 74%
“…18 several factors contributed to these delays, including fear of cancer treatment, financial challenges, delays in receiving biopsy results and the social stigma associated with cancer diagnosis. Furthermore, limited access to mammography and image-guided biopsy is pose a barrier to early diagnosis in Sudan 19 . Misinterpretation of symptoms and misdiagnosis by doctors were also significant factors leading to prolonged intervals in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The screening processes involves the use of different screening imaging tools chosen dependently according to the abnormal findings. These procedures even should available to asymptomatic individuals to help them in detecting and treatment of tumors before they in risk danger to their health, based on the Globocan 2020, 41.2 out of 100,000 Sudanese females agestandardized were infected by breast cancer comparing to cervix and ovarian cancer (8.7 and 6.7. respectively) [7] . For these reasons, this population-based study was intended to increase public awareness and improve knowledge of breast cancer diagnosis among Sudanese women.…”
Section: Discussionmentioning
confidence: 97%
“…Despite their good knowledge level, they justified their lack of experience through the following reasons: 59.5% did not have lump or pain, 14.19% were afraid of the results and 11.49% were ashamed or afraid to perform it. A popular explanation of these findings has been illustrated by Altirifi, H.I., et al 2022 [18] who showed that Sudanese women's unwillingness to undergo breast screening is due to the non-adequate quality improvement of health care authorities and the expansive of these procedure in our developing country and by Husain Elmalaika, et al 2022 [7] who stated that Sudan has essentially no programmers for cancer prevention, screening, or early detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them failed due to the scarcity of well-trained cytologists and cytopathologists. 14 , 15 Also, religious beliefs and behavioural aspects of conducting the diagnosis make it difficult to rely on it in cases of screening of ordinary checkups. 16 CC screening is not currently available through the public health system in Sudan.…”
Section: Introductionmentioning
confidence: 99%